A new type of hydrokinetic accumulator and its simulation in hydraulic lift with energy recovery system. (15th June 2018) - Latas, Waldemar; Stojek, Jerzy
Abstract: The article presents a model and a simulation study of a new type of hydrokinetic accumulator with increased energy storage density. The basic elements of the accumulator are: a flywheel of variable moment of inertia (due to inflow or outflow of hydraulic fluid) and a variable displacement pump/motor. The first part of the article describes the construction and operation principles of the developed accumulator with three specified work modes. A mathematical model of the presented hydrokinetic accumulator and its simulation in a hydrostatic lift system with energy recovery are given. The results of the numerical simulations carried out during charging and discharging of the accumulator (i.e. values of the stored kinetic and potential energy and chosen working parameters) are presented. It is shown that, due to energy storage and extraction, in both hydrostatic and rotating kinetic domains, charging and discharging may be decoupled from pressure level. Additionally, the accumulator has the ability to control the pressure in the hydraulic system. An example of the control algorithm is also presented in the paper. Highlights: New type of hydrokinetic accumulator with an increased energy storage density. The construction and operation principles of the developed accumulator. Model and a simulation study of the hydrokinetic accumulator. Simulation of the hydrostatic lift system with energy recovery.